Nd:YAG Laser Application for the Treatment of Retained Lens Fragment in the Anterior Chamber Following Cataract Surgery - Ali Mert Koçer; Bekir Eren Aksoy; Özge Uysal (Türk Oftalmoloji Dergisi)
Cataract surgery is the most frequently performed surgery worldwide. Although it is an effective surgical treatment option for improving patients’ visual acuity, various complications can occur postoperatively. One such complication is the presence of retained lens material in the anterior chamber, which can lead to intraocular inflammation, increased intraocular pressure, corneal edema, and endothelial cell loss. Treatment options include observation and surgical removal of the retained lens material. Another notable treatment option is the use of neodymium-doped yttrium aluminum garnet (Nd:YAG) laser to fragment the retained lens material. In this paper, we aim to present two cases from our clinic where Nd:YAG laser treatment was applied to patients with retained small lens fragments in the anterior chamber following cataract surgery. It was observed that in both patients, the retained lens fragments were resorbed by the first day after Nd:YAG laser treatment, and no complications developed.